Assessing sexual health literacy among Thai female adolescents in non-formal education: A mixed-methods study - Rapeepan Narkbubpha; Atcharawadee Sriyasak; Atiya Sarakshetrin; Pailin Thungthin (Belitung Nursing Journal)
Background: Adolescent pregnancy in Thailand and globally remains a major public health issue, often leading to significant health and social consequences. Among adolescents outside the formal education system, low levels of sexual and reproductive health literacy contribute to poor decision-making and increased risk of unintended pregnancy. Targeted, culturally sensitive interventions are essential to bridge these gaps and reduce associated hardships.